Pengaruh Senam Taichi dan Green Tea Terhadap Densitas Tulang pada Ibu Post Menopause di Kelurahan Timbang Galung, Kecamatan Siantar Barat, Pematangsiantar - Safrina Safrina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Osteoporosis can be found throughout the world and is still a problem in public health, especially in developing countries. This study aims to analyze the effect of Taichi and green tea exercises on bone density in postmenopausal women, using the pretest and posttest group with control design. The research subjects were 50 postmenopausal women in Pematangsiantar City. Data analysis using the Mann-Whitney-U and Wilcoxon test. The results showed that there were differences in bone density in the Tai-Chi + green tea gymnastics group before and after the intervention. The mean bone density T-score before intervention was 45.31 ± 10.54 and after intervention as many as 62.74 ± 10.18 with a mean difference of 17.46 ± 6.58; p